2019
DOI: 10.1186/s40425-019-0599-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and enhanced immunostimulatory activity of the DRD2 antagonist ONC201 in advanced solid tumor patients with weekly oral administration

Abstract: Background ONC201 is a small molecule antagonist of DRD2, a G protein-coupled receptor overexpressed in several malignancies, that has prolonged antitumor efficacy and immunomodulatory properties in preclinical models. The first-in-human trial of ONC201 previously established a recommended phase II dose (RP2D) of 625 mg once every three weeks. Here, we report the results of a phase I study that evaluated the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of weekly ONC201. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…Subsequently, in vivo studies in xenograft tumor models demonstrated improvement in antitumor efficacy including suppression of metastasis with once weekly administration relative to every three-week dosing [40] . Additionally, enhanced immune stimulatory activity was observed with weekly dosing relative to every three-week dosing [99] . Considering these observations, its benign safety profile, and wide therapeutic index, ONC201 was subsequently administered once weekly in clinical trials.…”
Section: Clinical Trialsmentioning
confidence: 97%
“…Subsequently, in vivo studies in xenograft tumor models demonstrated improvement in antitumor efficacy including suppression of metastasis with once weekly administration relative to every three-week dosing [40] . Additionally, enhanced immune stimulatory activity was observed with weekly dosing relative to every three-week dosing [99] . Considering these observations, its benign safety profile, and wide therapeutic index, ONC201 was subsequently administered once weekly in clinical trials.…”
Section: Clinical Trialsmentioning
confidence: 97%
“…Given that ONC201 has anti-tumor e cacy in preclinical models, the safety/tolerability and e cacy of ONC201 has been and is being tested in phase I and phase II clinical trials, respectively. Oral weekly ONC201 is well tolerated with very few adverse events and results in clinical activity in advanced solid tumors, including ECs (23,(53)(54)(55). The unique features of ONC201 to occupy DRD2 and DRD3 at physiological concentrations strengthens the excellent safety pro le of ONC201 in clinical trials (53).…”
Section: Discussionmentioning
confidence: 88%
“…Oral weekly ONC201 is well tolerated with very few adverse events and results in clinical activity in advanced solid tumors, including ECs (23,(53)(54)(55). The unique features of ONC201 to occupy DRD2 and DRD3 at physiological concentrations strengthens the excellent safety pro le of ONC201 in clinical trials (53). Importantly, multiple ongoing phase I/II trials of ONC201 as a signal agent or in combination with other agents in solid tumors and hematologic malignancies has been initiated in the US.…”
Section: Discussionmentioning
confidence: 96%
“…Recent preclinical and clinical data have hinted at an efficacy of ONC201 in several solid cancers including GBM [21][22][23]25,27 . Originally identified as an inducer of TRAIL, ONC201 inhibits D2-like dopamine receptors DRD2 and DRD3 and activates the mitochondrial protease ClpP, a key player in the mitochondrial unfolded protein response 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…This results in dual inactivation of Akt/ERK signaling that drives Foxo3a-mediated TRAIL gene induction to promote pro-apoptotic and anti-proliferative effects in tumor cells, but not in normal cells [16][17][18][19][20] . With p53-independency, low toxicity and excellent penetration of the BBB, ONC201 is currently being evaluated in multiple clinical trials for select advanced malignancies, including myeloma, leukemia, lymphoma, endometrial cancer, high grade glioma, and other solid tumors [21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%